ANALISIS KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Rosa Fitri; Ernie Hendrawaty; Ahmad Faisol (Yayasan Nusantara Hasana Berdikari, 2026)
Dividend policy is a crucial decision for manufacturing companies as it must balance shareholder interests with the company’s needs for future business sustainability. This study aims to examine the effect of liquidity (CR), leverage (DER), profitability (ROE), and company size (Size) on dividend policy (DPR) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. This study uses is quantitative approach utilizing secondary data obtained from the annual reports of manufacturing companies published on the company’s official website and the IDX. The research sample includes 34 manufacturing companies selected using a purposive sampling method. The data analysis method used is panel data regression analysis using Eviews 12 software. The research findings indicate that liquidity (CR) and company size (Size) have a positive and significant effect on DPR, while leverage (DER) and profitability (ROE) do not affect dividend policy (DPR). Simultaneously, all independent variables have a significant effect on dividend policy. These results indicate that cash availability and company scale are the main factors for companies in predicting dividend receipts.